2017
DOI: 10.14444/4023
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Lordotic cages on creating Sagittal Balance in the CMIS treatment of Adult Spinal Deformity

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 60 publications
0
14
2
1
Order By: Relevance
“…Other authors found correction capability of the hyperlordotic cages through the anterior and lateral approach highly efficient. [8][9][10] Although not much could be found in the literature, the complication rate is seemingly low and not significantly dissimilar to ours. 11,12 In our experience, we had fewer postoperative neurological dysfunctions after using the hyperlordotic XLIF cages as compared with regular XLIF cages.…”
Section: Discussioncontrasting
confidence: 63%
“…Other authors found correction capability of the hyperlordotic cages through the anterior and lateral approach highly efficient. [8][9][10] Although not much could be found in the literature, the complication rate is seemingly low and not significantly dissimilar to ours. 11,12 In our experience, we had fewer postoperative neurological dysfunctions after using the hyperlordotic XLIF cages as compared with regular XLIF cages.…”
Section: Discussioncontrasting
confidence: 63%
“…In previous studies, LIF was shown to have improved segmental sagittal alignment [21], with an increase in disk height of 41.9%-83% and an increase in foraminal height of 13.5%-83% [22,23]. Anand et al [23] reported an 8.1° increase in segmental lordosis in ASD cases treated with LIF using a 10° cage. In an investigation of 80 patients (mean fusion level, 1.5 levels), Shiga et al [24] found that the acquired lordotic angle was 3.8° after LIF with 6° lordotic cages.…”
Section: Discussionmentioning
confidence: 93%
“…This cage is useful for the correction of ASD to restore disk height in cases where degeneration is the main cause of the deformity [3]. In previous studies, LIF was shown to have improved segmental sagittal alignment [21], with an increase in disk height of 41.9%-83% and an increase in foraminal height of 13.5%-83% [22,23]. Anand et al [23] reported an 8.1° increase in segmental lordosis in ASD cases treated with LIF using a 10° cage.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, LLIF resulted in improved local sagittal alignment [18]. In addition, an increase in disc height from 41.9% to 83% and an increase in foraminal height from 13.5% to 83% were observed after LLIF [19,20]. As for the segmental acquired lordotic angle achieved with LLIF, Anand et al [20] reported an 8.1° increase in segmental lordosis in adult spinal deformity cases with LLIF, using a 10° cage.…”
Section: Discussionmentioning
confidence: 95%